Pivovarství - Artýszková, Jana (Vysoké učení technické v Brně. Fakulta chemická, 2009)
Cílem teoretické části bakalářské práce bylo prostudovat a zpracovat problematiku výroby piva se zaměřením na české podmínky a klasickou technologii. V teoretické práci byla stručně shrnuta historie tohoto průmyslového odvětví a některé moderní metody, které umožňují větší efektivitu práce a současně ekonomickou výhodnost. Experimentální část práce byla provedena v malém pivovaře v České republice s výstavem přibližně 10 000 hl za rok. V pivovaře byly sledovány vybrané parametry jak v průběhu vaření a kvašení piva, tak při výstupní kontrole při stáčení do sudů a plastových lahví. Sledované znaky byly: sacharizace předku a mladiny, kontrola mikrobiologické kontaminace na spilce a ve sklepě, obsah oxidu uhličitého při dokvašování a u hotového produktu pH a barva piva.

The aim of the theoretical part of the thesis is the study and the treatment of the problem of the manufacturing of beer, focused on the czech conditions and classical Czech technology. Within the theoretical part the history of this branch of industry together with the modern methods, enabling greater productivity of beer production, are summarized. Experimental part of the thesis was carried out in a small brewery in Czech republic, producing aproximately 10 000 hl per year. In this brewery the selected parameters were studied not only in the course of cooking and fermentation of beer, but during the output control in racking to the drums and plastic bottles, as well. The studied parameters were as follows: the sugar content of front and wort, the control of microbiological contamination in fermenting cellar and in beer-storage cellar, the content of CO2 by last stage of fermentation and pH- value and color by the end-product.
Brewing industry
Keywords: pivo; pivovarství; dekokční rmutování; mladina; kvašení; kvasinky; filtrace; barva piva; pH; beer; brewing; decoction mashing; wort; fermentation; yeast; filtration; color of beer; pH